Strategi Guru PAI dalam Penanaman Karakter Peserta Didik di SMK Negeri 2 Surakarta - Lulu Amira; Mohammad Zakki Azani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the strategies excuted by Islamic Religious Education (PAI) teachers in instilling character in students at SMK Negeri 2 Surakarta. This is useful to determine the extent of teacher success in realizing graduates with character through the values of integrity, independence, caring, and responsibility in academic and non-academic activities. The background of the study is based on the importance of character in the vocational school environment, where students need to be equipped with good religious, moral, and ethical values. The research method uses a qualitative approach with observation techniques, in-depth interviews with one of the PAI teachers, and analysis of documents related to the PAI curriculum. The results of the study indicate that the main strategies of PAI teachers which include habituation, role models, intensive guidance, and the role as a motivator provide quite effective results in instilling character such as discipline, empathy, independence, responsibility that can be applied through their daily activities. However, there are several challenges and obstacles experienced by teachers in carrying out this task such as limited facilities, integration of the religious curriculum with vocational subjects, differences in backgrounds between students, and low interest of some students in PAI subjects also require further innovation. The study concluded that a structured and adaptive Islamic Religious Education (PAI) teacher strategy can increase the effectiveness of character education at SMK Negeri 2 Surakarta. The implementation of this strategy demonstrates that character education is not merely theoretical but also integrated into the learning process and social interactions at school. This investigation contributes to the development of Islamic education in vocational schools, with suggestions for extended investigation into the long-term implications of student behavior.